Analysis Of The Effect Of Work Value, Morale, And Mastery Of Information Technology On The Performance Of State Junior High School Teachers In Mojokerto Regency East Java - Elfia Nora; Imam Bukhori; Sopiah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Work values, mastery of information technology, and high morale are a unit that will shape teacher performance, where teachers are required to have a set of competencies that they must have in carrying out their profession as an educator. The objectives of this study are: to test the effect of work value on the performance of teachers of State Junior High School 2 Trawas and State Junior High School 1 Sooko, Mojokerto Regency, b) to Test the influence of morale on the performance of teachers of State Junior High School 2 Trawas Mojokerto Regency, c) Test the influence of mastery of information technology on the performance of teachers of State Junior High School 2 Trawas and State Junior High School 1 Sooko, Mojokerto Regency.  This research was conducted on the teachers of State Junior High School 2 Trawas, Mojokerto Regency, which was originally estimated to be 70 teachers, but from the latest data received accompanied by a questionnaire that returned 25 people, so that the scope of the research object was developed to State Junior High School 1 Sooko which has the same characteristics as State Junior High School 2 Trawas and respondents of teachers of State Junior High School 1 Sooko totaling 40 people. The sampling technique used is saturated sampling. The results showed: 1) There was a positive and significant influence between the work value on the performance of State Junior High School 2 Trawas and State Junior High School 1 Sooko Mojokerto with  t counting i.e. 3.0192) There was a positive and significant influence between morale on the performance of teachers of State Junior High School 2 Trawas and State Junior High School 1 Sooko Mojokerto, with t counting i.e. 4,551 3) There is a positive and insignificant influence between mastery of information technology on the performance of teachers of State Junior High School 2 Trawas and State Junior High School 1 Sooko Mojokerto, with t counting i.e. 2,387.